Measuring the Effect of University Students Psychological Resilience on Their Valuation of Sustainability in Entrepreneurship - Barrera-Verdugo, G (TAYLOR & FRANCIS AS, 2023)
For decades, resilience and sustainability have been considered to be two concepts that are related on a systemic and organizational level; however, little has been studied regarding the influence of psychological resilience on the valuation of sustainable ventures. This research analyzes the responses of 240 university students in Chile to an online self-report survey through logistic regressions to determine the effect of psychological resilience on the appreciation of sustainable entrepreneurship from an environmental and social perspective, measuring the moderating effect of age cohort and gender. The results supported that students with a higher self-perceived resilience that is measured by the Brief Resilience Scale (BRS) also show a higher appreciation toward sustainability in entrepreneurship. A moderating effect of belonging to the centennial generation on the relationship between psychological resilience and valuation of sustainable ventures has also been supported. The findings contribute to understanding how personal adaptation, which is part of resilience, influences the perceived importance of sustainability in entrepreneurship, which is a perspective related to organizational innovation.